Diagnostic accuracy and comparison of BIPSS in response to lysine vasopressin and hCRH. Issue 3 (March 2018) - Jarial, Kush Dev Singh; Bhansali, Anil; Gupta, Vivek; Singh, Paramjeet; Mukherjee, Kanchan K; Sharma, Akhilesh; Vashishtha, Rakesh K; Sukumar, Suja P; Sachdeva, Naresh; Walia, Rama
Abstract : Context: Bilateral inferior petrosal sinus sampling (BIPSS) using hCRH is currently considered the 'gold standard' test for the differential diagnosis of ACTH-dependent Cushing's syndrome (CS). Vasopressin is more potent than CRH to stimulate ACTH secretion as shown in animal studies; however, no comparative data of its use are available during BIPSS. Objective: To study the diagnostic accuracy and comparison of hCRH and lysine vasopressin (LVP) stimulation during BIPSS. Patients and methods: 29 patients (27-Cushing's disease, 2-ectopic CS; confirmed on histopathology) underwent BIPSS and were included for the study. Patients were randomized to receive hCRH, 5 U LVP or 10 U LVP during BIPSS for ACTH stimulation. BIPSS and contrast-enhanced magnetic resonance imaging (CEMRI) were compared with intra-operative findings of trans-sphenoidal surgery (TSS) for localization and lateralization of the ACTH source. Results: BIPSS correctly localized the source of ACTH excess in 29/29 of the patients with accuracy of 26/26 patients, using any of the agent, whereas sensitivity and PPV for lateralization with hCRH, 5 U LVP and 10 U LVP was seen in 10/10, 6/10; 10/10, 8/10 and 7/7, 6/7 patients respectively. Concordance of BIPSS with TSS was seen in 20/27, CEMRI with BIPSS in 16/24 and CEMRI with TSS in 18/24 of patients for lateralizing the adenoma. Most of the side effects were transient and were comparable in all the three groups. Conclusion: BIPSS using either hCRH or LVP (5 U or 10 U) confirmed the source of ACTH excess in all the patients, while 10 U LVP correctly lateralized the pituitary adenoma in three fourth of the patients.